Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Keterampilan Mengurutkan Pecahan pada Siswa Kelas VI SD 005 Tarakan - Kristiani Atasage (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Application of stad type cooperative learning model to improve fraction sorting skills in grade VI students of SD 005 Tarakan. The type of research used is Classroom Action Research which consists of 4 stages, namely planning, implementation, observation, and reflection. The subjects in this study were grade VI students of SD Negeri 005 Tarakan in the second semester of the 2021/2022 academic year as many as 28 students consisting of 14 male students, and 14 female students. The instruments used for data collection are observation sheets and tests. Data analysis techniques used to analyze data obtained in the field are descriptive. The results of data analysis show that STAD cooperative learning can improve fraction sorting skills in grade VI students of SD Negeri 005 Tarakan